RESEARCH ON THE PROPERTIES OF MATERIALS PREPARED BY ELECTROSPINING FROM PVA SOLUTIONS BASED ON PLANT EXTRACTS - LIASHOK, IRINA; SIKORA, ANDRII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
In this study, nonwoven fibrous materials (NFM) were obtained from aqueous extracts of oak bark (Quercus cortex) and blue gum eucalyptus (Eucalyptus globulus) by electrospinning under controlled laboratory conditions. The process was carried out at a voltage of 30 kV and an electrode distance of 16–18 cm, which ensured the stable formation of polymer jets. Optical microscopy confirmed that the chosen parameters allowed the fabrication of fibers with diameters ranging from 1 to 3 µm, characteristic of nanofibrous systems with a high surface-to-volume ratio and favorable morphological properties. It was proven that the water vapor permeability of NFM based on the aqueous extract of oak bark Quercus cortex with a sample thickness of 0.15 mm is 1.843 mg/cm², while for NFM based on the aqueous extract of blue gum eucalyptus Eucalyptus globulus with a sample thickness of 0.07 mm it is 1.471 mg/cm². It was demonstrated that the vapor permeability of electrospun NFMs exceeded that of films prepared from similar polymer solutions by 400–500%, which is explained by the very high specific surface area, the presence of open porous channels, and the developed capillary structure that facilitates diffusion and moisture transport. Thermal stabilization of NFMs for 3 h at 80 °C increased the maximum water absorption of Quercus cortex-based samples by 10.7% and of Eucalyptus globulus-based samples by 18.6%. Moreover, stabilization of the corresponding film samples enhanced both the maximum and the equilibrium degree of water absorption, which indicates the formation of more structurally organized and stable materials. This phenomenon can be attributed to the presence of tannins and polyphenolic compounds in aqueous plant extracts, which promote intermolecular hydrogen bonding, increase the degree of supramolecular ordering, and thereby contribute to the overall stabilization of the polymer matrix.
Keywords: electrospinning; polyvinyl alcohol; nonwoven fibrous material; aqueous extracts of medicinal plants